Curriculum interdependence in the preparation of the engineering and economic and financial technique of the future commercial marine officers - Carmen Elena Coca (Technium Social Sciences Journal, 2020)
The education and training of the future commercial naval officers has reached a high quality international level, recognized both by the beneficiaries and by the bodies of evaluation of the activity of the institutions of higher education of the navy. The training of the commercial naval officers involves knowledge and skills in the technical field and in other complementary fields. The current challenges related to safety, security and economic efficiency lead to the consolidation of the level of education and training of commercial naval officers, through the interdependence and diversification of the curricula in the world economy of shipping, finance of the maritime industry and the specialized labour market.